Decreasing The Level of Depression for Earthquake Victims Through Counseling With a Motivational Interviewing Approach - Idris, Baiq Nurainun Apriani; Istianah, Istianah; Hadi, Irwan (Universitas Muhammadiyah Semarang, 2020)
The earthquake that occurred in Lombok cause a post-earthquake depression that affects mental and psychological changes.Â Â Motivational interviewing is a non-pharmacological action with counseling therapy to increase the motivation and change ambivalence to avoid or reduce depression of post-earthquake sufferers. This research aims to find out the effectiveness of motivational interviewing on the reduction of depression in post-earthquake in the North Lombok Regency. This research using a quasi-experimental methodology with pre-post test design, where research is carried out in North Lombok using a purposive sampling technique. The study shows the effectiveness of Motivational Interviewing on the reduction of depression in victims of the post-earthquake intervention group. Natural disasters that occur such as earthquakes with the resulting impact can cause vulnerability to victims that influence physically and psychologically. Non-pharmacological interventions Motivational Interviewing (MI) in respondents with moderate and severe depression can reduce the level of depression in post-earthquake victims.